Sistem Monitoring Indek Kualitas Udara Berbasis Open Meteo Air Quality API - Rahayuda, I Gede Surya; Santiari, Ni Putu Linda (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 3 (2024): JELIKU Volume 12 No 3, February 2024DO - 10.24843/JLK.2023.v12.i03.p22, 2024)
This research aims to develop an air quality monitoring system based on the Open Meteo API and OpenStreetMap API using the Software Development Life Cycle (SDLC) approach. By utilizing latitude and longitude data, users can see the air quality index (AQI) at a location with a default forecast for one day every hour. Users also have the option to configure the location and number of days for the forecast. Through trials, this website succeeded in determining AQI values based on user configuration. In addition, this system uses color as a visual representation of AQI categories based on united states air quality index standards, making it easier for users to understand the level of health risk. The development of this system involves the SDLC method to ensure a smooth development process from design to implementation. Apart from increasing the accuracy of AQI mapping, the use of the OpenStreetMap API also allows location identification based on geographic coordinates. Overall, this research contributes to the understanding and monitoring of air quality with an approach that is easy to access and understand for users. Keywords : aqi, api, open meteo, vercel, github